Heat exchangers for cardioplegia systems: In vitro study of four different concepts - Drummond, M.; Novello, W. P.; de Arruda, ACF; Braile, D. M. (Blackwell Publishing, 2003)
The aim of this work is the evaluation of four different heat exchangers used for myocardium during cardioplegic system in cardiac surgeries. Four types of shell and tube heat exchangers made of different exchange elements were constructed, as follows: stainless steel tubes, aluminium tubes, polypropylene hollow fiber, and bellows type. The evaluation was performed by in vitro tests of parameters such as heat transfer, pressure drop, and hemolysis tendency. The result has shown that all four systems tested were able to achieve the heat performance, and to offer low resistance to flow, and safety, as well as have low tendency to hemolysis. However, we can emphasize that the bellows type heat exchanger has a significant difference with regard to the other three types.
Keywords: blood cardioplegia; heat exchangers; myocardial preservation